2014
DOI: 10.1513/annalsats.201310-339fr
|View full text |Cite
|
Sign up to set email alerts
|

Lung Microbiome for Clinicians. New Discoveries about Bugs in Healthy and Diseased Lungs

Abstract: Microbes are readily cultured from epithelial surfaces of the skin, mouth, and colon. In the last 10 years, culture-independent DNAbased techniques demonstrated that much more complex microbial communities reside on most epithelial surfaces; this includes the lower airways, where bacterial culture had failed to reliably demonstrate resident bacteria. Exposure to a diverse bacterial environment is important for adequate immunological development. The most common microbes found in the lower airways are also foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 99 publications
1
112
0
Order By: Relevance
“…Sputum culture has traditionally been used for the identification of bronchial infection by bacteria; however, currently available techniques are not suitable for the identification of up to 80% of microorganisms inhabiting mucosal surfaces [39]. In this context, molecular culture independent techniques have identified bacteria previously not amenable to culture.…”
Section: Microbioma and Exacerbations Of Chronic Obstructive Pulmonarmentioning
confidence: 99%
“…Sputum culture has traditionally been used for the identification of bronchial infection by bacteria; however, currently available techniques are not suitable for the identification of up to 80% of microorganisms inhabiting mucosal surfaces [39]. In this context, molecular culture independent techniques have identified bacteria previously not amenable to culture.…”
Section: Microbioma and Exacerbations Of Chronic Obstructive Pulmonarmentioning
confidence: 99%
“…To address this complexity, systems biology approaches will be needed. In fact, they have already begun to be applied to several respiratory diseases too [49][50][51][52][53][54][55] .…”
Section: Systems Biology: What Does It Deliver?mentioning
confidence: 99%
“…Previously thought to be sterile, data suggest the presence of bacterial DNA in the lower respiratory tract, some of which is similar to that of the upper airway, but some of which appears to be over-represented in the lower airways [1012]. Although concerns about acquisition and contamination of lower airway specimens through the necessity of traversing the upper airway in humans are present, careful studies comparing the upper and lower airway microbiota, studies using explanted lungs at the time of transplantation and mouse studies have demonstrated that, although present in low numbers in healthy lungs, there is a lower airway microbial presence that is distinct from that of the upper airway [1317].…”
Section: The Respiratory Tract Microbiomementioning
confidence: 99%